PENGARUH PENERAPAN ETIKA PROFESI, KOMITMEN ORGANISASI DAN KECERDASAN EMOSIONAL TERHADAP PENINGKATAN PROFESIONALISME AKUNTAN PUBLIK - Rahman, Alfi Dwi; Hardana, Ali (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Sharia banking in Indonesia continues to develop rapidly over time. This growth cannot be separated from problematic financing. So, banks must maintain the health of the bank itself. This research aims to examine the influence of Return On Assets (ROA), Return On Equity (ROE), and Financing To Deposit Ratio (FDR) on non-performing financing (NPF). The population of this research is 10 sharia banks registered with BUS. The type of research used in this research is quantitative research, using secondary data. Sourced from the official websites of each bank, the 2020 - 2022 period uses quarterly financial reports. The analysis technique used is multiple linear regresion. The results of this research are that Return On Assets (ROA) does not have effect on the NPF of Sharia Commercial Banks in Indonesia. (2) ROE has a negative effect on the NPF of Sharia Commercial Banks in Indonesia. These results show that the higher the bank's profits, the lower the financing problem and vice versa. (3) FDR influences the NPF of Sharia Commercial Banks in Indonesia. Suggestions for further research include adding macroeconomic factors to the independent variables for problematic financing, interest rates, exchange rates and inflation